Cloud-based intelligent informative engineering for society 5.0 - Kishor, Kaushal; Saxena, Neetesh; Pandey, Dilkeshwar (Boca Raton : Chapman & Hall/CRC Press, 2023)
"Cloud-based Intelligent Informative Engineering for Society 5.0 is a model for the dissemination of cutting-edge technological innovation and assistive devices for people with physical impairments. This book showcases Cloud-based, high-performance Information systems and Informatics-based solutions for the verification of the information support requirements of the modern engineering, healthcare, modern business, organization, and academic communities"--
OCLC-licensed vendor bibliographic record.
Keywords: Expert systems (Computer science); Cloud computing; Society 5.0.; COMPUTERS / Machine Theory; COMPUTERS / Artificial Intelligence